2022
DOI: 10.1039/d2cp01681h
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of emitter–emitter and emitter–plasmonic surface separations dictate photoluminescence enhancement in a plasmonic field

Abstract: The brightness of an emitter can be enhanced by metal-enhanced fluorescence, wherein the excitonic dipole couples with the electromagnetic field of the surface plasmon. Herein, we experimentally map the landscape...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Strong coupling usually involves two systems, where one needs to be strongly confined and another needs to possess a strong transition dipole moment. The strength of such coupling can be given as g = μ e | E vac |∝ μ e /√ V , where g is the coupling strength, E vac is the vacuum field, and V is the mode volume. , In recent times, strongly coupled nanoscale assemblies with coupling between local surface plasmon resonance and excitons, excitons with photons, etc., ,,, have attracted considerable attention from academia and industry owing to their potential applications in fields of artificial light harvesting, thresholdless lasing, sensing, quantum information processing, optical computing, etc. In fact, it has been recently proposed that strong coupling between two suitable interacting systems such as exciton–exciton, exciton–plasmon, exciton–photon, and photon–plasmon can produce future-generation materials for various optoelectronic applications. Strong coupling has also been demonstrated in hybrid nanosystems comprising plasmonic nanoparticles and cyanine dye J-aggregates . Interestingly, it has been demonstrated that strong coupling can also lead to an interesting process known as valley splitting, where the observed emission band gets split into two distinct emission bands due to the lifting of the degeneracy of the two existing excitonic states of the emitting species (QDs). , The valley splitting phenomenon has been observed in the plasmonic absorption band of nanomaterials in the presence of inorganic excitons (QDs), , organic excitons (aggregates), , and also in the presence of two-dimensional transition-metal dichalcogenides. , Very recently, Omata and co-workers have shown that strong exciton–exciton coupling between PbSe QDs can lead to valley splitting of the QD emission, and they have also shown that the interdot distance can control the extent of valley splitting .…”
Section: Introductionmentioning
confidence: 99%
“…Strong coupling usually involves two systems, where one needs to be strongly confined and another needs to possess a strong transition dipole moment. The strength of such coupling can be given as g = μ e | E vac |∝ μ e /√ V , where g is the coupling strength, E vac is the vacuum field, and V is the mode volume. , In recent times, strongly coupled nanoscale assemblies with coupling between local surface plasmon resonance and excitons, excitons with photons, etc., ,,, have attracted considerable attention from academia and industry owing to their potential applications in fields of artificial light harvesting, thresholdless lasing, sensing, quantum information processing, optical computing, etc. In fact, it has been recently proposed that strong coupling between two suitable interacting systems such as exciton–exciton, exciton–plasmon, exciton–photon, and photon–plasmon can produce future-generation materials for various optoelectronic applications. Strong coupling has also been demonstrated in hybrid nanosystems comprising plasmonic nanoparticles and cyanine dye J-aggregates . Interestingly, it has been demonstrated that strong coupling can also lead to an interesting process known as valley splitting, where the observed emission band gets split into two distinct emission bands due to the lifting of the degeneracy of the two existing excitonic states of the emitting species (QDs). , The valley splitting phenomenon has been observed in the plasmonic absorption band of nanomaterials in the presence of inorganic excitons (QDs), , organic excitons (aggregates), , and also in the presence of two-dimensional transition-metal dichalcogenides. , Very recently, Omata and co-workers have shown that strong exciton–exciton coupling between PbSe QDs can lead to valley splitting of the QD emission, and they have also shown that the interdot distance can control the extent of valley splitting .…”
Section: Introductionmentioning
confidence: 99%
“…The separation between fluorophores and the surface of the plasmonic nanostructure surface is also crucial, with typical optimum values in the range of 5–90 nm. The field is not limited to organic fluorophores. Metal NPs can act as optical antennae and result in enhanced emission for nanomaterials like quantum dots. , One of the major matters of concern in the implementation of MEF is reproducibility, ,, which is affected by the size distribution of metallic NPs, uncontrolled deposition during preparation of the NP layer, distribution in distances between the probe and surface of the NPs and diffusion of target molecules. ,, Aggregation of the fluorophores is another possible factor.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling light-matter interactions at the nanoscale dimensions has opened up novel prospects in the miniaturization of optoelectronic systems such as light-emitting devices, plasmonic circuits, solar cells, and quantum optics. Among various light-activated nanoscale materials, plasmonic nanoparticles are promising for such applications, owing to their ability to confine light at smaller dimensions and produce intense electric fields. Surface plasmon resonances in noble metal nanoparticles such as Au and Ag arise from the collective oscillations of their conduction electrons which are characterized by huge extinction coefficients (ε ∼ 10 9 –10 10 M –1 cm –1 ) and effective oscillator strengths ( f ∼ 10 4 –10 5 ). , The giant transition dipole moments in these plasmonic systems are responsible for intense electric fields at their resonant frequencies. The surface plasmon resonances in metallic nanoparticles are highly sensitive to their size, shape, and composition, permitting high spectral and electric field tunability. , Coupling of plasmonic resonances with excitons (bound electron–hole pairs) in molecular systems has significant consequences on their optoelectronic properties: weak coupling results in the enhancement of Raman , and fluorescence signals of the molecules, whereas strong coupling leads to the formation of hybrid plasmon-exciton states, often called as plexciton states. ,, …”
Section: Introductionmentioning
confidence: 99%